Research on the spatial characterization of herder grazing intensity supported by mobile phone signaling data - Qiao, Zhanming; Zheng, Min; Li, Zheng; Dong, Quanmin; Zhang, Chunping; Yu, Yang; Cao, Quan (Frontiers in Ecology and Evolution, 2025)
IntroductionMobile phone signaling data have become one of the main types of data used to carry out spatial mobility analysis, but no research has simulated herders’ grazing intensity by using this measure.MethodsIn this paper, based on herders’ mobile phone signaling data, herders’ network centrality and herders’ network connection intensity were established. The equal weight average method was employed to simulate herders’ grazing intensity, with empirical analyses conducted in the Henan Mongolian Autonomous County.ResultsThe findings indicated that: 1) herders’ mobile phone signaling data can quantitatively represent grazing intensity, and when combined with the density and elevation distribution of settlements in Henan County, it reveals that the spatial distribution of grazing intensity aligns with the trajectory of herders’ summer grazing activities. 2) The spatial characteristics of the centrality of the herders’ mobility network exhibited a concentrated point-like ring structure, primarily centered on the townships of Duosong and Youganning, with a decreasing spread outward. 3) The spatial characteristics of the intensity of herders’ mobility ties showed a circular distribution for the overall degree of network ties, which was primarily characterized by low ties. The intensity of mobility links among townships was low, with higher intensity observed only at the junctions of townships, indicating limited mobility among herders in Henan County regarding their herding behavior. 4) The grazing intensity of herders in Henan County was primarily characterized by light grazing.DiscussionResearch shows that the spatialized simulation model based on big data provided in this paper can accurately portray the spatial distribution characteristics of grazing intensity in the study area, ,and effectively and conveniently serve grassland resource management.